Optimal Threshold of Controlled Attenuation Parameter for Detection of HIV-Associated NAFLD With Magnetic Resonance Imaging as the Reference Standard. (25th September 2020) - Ajmera, Veeral H; Cachay, Edward R; Ramers, Christian B; Bassirian, Shirin; Singh, Seema; Bettencourt, Richele; Richards, Lisa; Hamilton, Gavin; Middleton, Michael; Fowler, Katie; Sirlin, Claude; Loomba, Rohit
Abstract: Background: Controlled attenuation parameter (CAP) is an ultrasound-based point-of-care method to quantify liver fat; however, the optimal threshold for CAP to detect pathologic liver fat among persons living with human immunodeficiency virus (HIV; PLWH) is unknown. Therefore, we aimed to identify the diagnostic accuracy and optimal threshold of CAP for the detection of liver-fat among PLWH with magnetic resonance imaging proton-density fat fraction (MRI-PDFF) as the reference standard. Methods: Patients from a prospective single-center cohort of PLWH at risk for HIV-associated nonalcoholic fatty liver disease (NAFLD) who underwent contemporaneous MRI-PDFF and CAP assessment were included. Subjects with other forms of liver disease including viral hepatitis and excessive alcohol intake were excluded. Receiver operatic characteristic (ROC) curve analysis were performed to identify the optimal threshold for the detection of HIV-associated NAFLD (liver fat ≥ 5%). Results: Seventy PLWH (90% men) at risk for NAFLD were included. The mean (± standard deviation) age and body mass index were 48.6 (±10.2) years and 30 (± 5.3) kg/m 2, respectively. The prevalence of HIV-associated NAFLD (MRI-PDFF ≥ 5%) was 80%. The M and XL probes were used for 56% and 44% of patients, respectively. The area under the ROC curve of CAP for the detection of MRI-PDFF ≥ 5% was 0.82 (0.69–0.95) at the cut-point of 285 dB/m. The positive predictive value of CAP ≥ 285 dB/m was 93.2% in this cohort with sensitivity of 73% and specificity of 78.6%. Conclusions: The optimal cut-point of CAP to correctly identify HIV-associated NAFLD was 285 dB/m, is similar to previously published cut-point for primary NAFLD and may be incorporated into routine care to identify patients at risk of HIV-associated NAFLD. Abstract : CAP values vary based on the underlying cause of liver disease. Here we establish the diagnostic accuracy (c = 0.82) and optimal cut-point (285 dB/m) of CAP in PLWH at risk for NAFLD with MRI proton-density-fat-fraction as the reference.